Effect of Environmental Disturbance on the Population of Sandflies and Leishmania Transmission in an Endemic Area of Venezuela - Elsa Nieves; Luzmary Oraá; Yorfer Rondón; Mireya Sánchez; Yetsenia Sánchez; Masyelly Rojas; Maritza Rondón; Maria Rujano; Nestor González; Dalmiro Cazorla (Journal of Tropical Medicine)
The exploitation of new wilderness areas with crops is increasing and traditional crop substitution has been modified by new more productive crops. The results show the anthropogenic disturbance effect on the sandflies population and Leishmania transmission in endemic areas of Venezuela. Three agroecosystems with variable degrees of ecological disturbance, forest (conserved), cacao (fragmented), and orangery (disturbed), were selected. Four methods to sandfly capture were used; the specimens were identified and infected with Leishmania. Diversity, population structure, ANOVA, Tukey test, and simple correlation analysis were carried out. Shannon traps were able to capture 94.7% of the total sandflies, while CDC light traps, Sticky traps, and direct suction just captured 2.2%, 1.2%, and 0.9%, respectively. The results showed the effect of ecological disturbance degree on the composition of sandflies and population structure, revealing a dominance level increased but decreased on the diversity and richness of sandflies species in the greatest ecological disturbance area in relation to areas with less organic disturbance. Environments more disturbed cause adaptability of certain species such as Lutzomyia gomezi and Lutzomyia walkeri. These changes on the composition of sandflies population and structure emerging species could cause increasing of leishmaniasis transmission.